A new species of Korinnis Günther from the Philippines (Phasmatodea: Prisopodidae: Korinninae) - Gottardo, Marco (Zootaxa, 2008)
The Philippine phasmid fauna is highly biodiverse (Hennemann & Conle 2007), but several taxonomic groups are as yet little understood. An obvious example is the superfamily Aschiphasmatoidea Brunner von Wattenwyl, 1893. Philippine representatives of this ancestral clade (Zompro 2004) fall into the Southeast-Asian subfamilies Aschiphasmatinae (Aschiphasmatidae), and Korinninae (Prisopodidae). Altogether, only nine species have been recorded from the archipelago, although some species cited by Redtenbacher (1906) and Bruner (1915) appear to be erroneous records. Zompro (2004: 90) indicates that Philippine reports of Orthomeria (Orthomeria) pandora (Westwood, 1859) and O. (O.) forstenii (de Haan, 1842) have been based on misidentifications. Additionally, Aschiphasma annulipes Westwood, 1834 is here excluded from the Philippine fauna; definite distribution records of this species include Indonesia (Kalimantan, Java and Sumatra), Malaysia, Thailand, Vietnam, and north India.